2023
DOI: 10.1126/sciimmunol.abq6352
|View full text |Cite
|
Sign up to set email alerts
|

A human model of asthma exacerbation reveals transcriptional programs and cell circuits specific to allergic asthma

Abstract: Asthma is a chronic disease most commonly associated with allergy and type 2 inflammation. However, the mechanisms that link airway inflammation to the structural changes that define asthma are incompletely understood. Using a human model of allergen-induced asthma exacerbation, we compared the lower airway mucosa in allergic asthmatics and allergic non-asthmatic controls using single-cell RNA sequencing. In response to allergen, the asthmatic airway epithelium was highly dynamic and up-regulated genes involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…The exact mechanism determining whether a pro- or anti-inflammatory monocyte response is mounted remains to be determined. The presence of Th2 cells in the tissue of AR patients is a likely candidate (as demonstrated for the airways of patients with allergic asthma; Alladina et al, 2023 ; Cho et al, 2016 ), either or not boosted by local chemokines, as those were prominently found among differentially expressed ligand–receptor interaction pairs described in Fig. S4, E and F .…”
Section: Discussionmentioning
confidence: 82%
“…The exact mechanism determining whether a pro- or anti-inflammatory monocyte response is mounted remains to be determined. The presence of Th2 cells in the tissue of AR patients is a likely candidate (as demonstrated for the airways of patients with allergic asthma; Alladina et al, 2023 ; Cho et al, 2016 ), either or not boosted by local chemokines, as those were prominently found among differentially expressed ligand–receptor interaction pairs described in Fig. S4, E and F .…”
Section: Discussionmentioning
confidence: 82%
“…This study highlights that macrophage soluble products may account for some of these discrepancies. Notably, recent studies in both humans and mice have identified the importance of macrophage-epithelial interactions in wound repair and asthma ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also detected an interaction of basal EpC CCL26 with a different chemotactic receptor, CCR2 , on IL1B monocyte-derived macrophages in eCRSwNP, but not in FCER2 monocyte-derived macrophages or FN1 activated tissue-resident macrophages in eCRSwNP. Macrophages expressing CCR2 have been implicated in asthma pathogenesis due to their expansion after allergen challenge in human asthmatics ( 37 ) and have been identified as potential precursors for intra-epithelial macrophages and alternatively-activated macrophages in mouse asthma models ( 38 ). Whereas CCR2 is conventionally thought of as a receptor for the monocyte chemoattractant CCL2 (which encodes MCP-1), binding of CCL26 to CCR2 has been reported to prevent the ability of monocytes to response to monocyte chemokines such as MCP-1 ( 66 ); therefore we propose that this CCL26-CCR2 interaction may underlie the lack of expansion in IL1B monocyte-derived macrophages in eCRSwNP ( Supplementary Figure 1C ) compared to alternatively-activated macrophage populations ( Figure 1D ).…”
Section: Discussionmentioning
confidence: 99%
“…Further work utilising scRNAseq showed heterogeneity within Th2 cell populations and identified a subset of pathogenic IL-9-expressing Th2 cells that was increased in allergic asthmatic individuals compared to allergic individuals without asthma [ 72 ]. Strikingly, post-allergen challenge, Th2 cells were only present in the airways in asthma, and airway epithelial cells demonstrated a dramatically altered transcriptional response in subjects with asthma but not in those with allergy alone [ 73 ]. The online resource Human Lung Cell Atlas integrates multiple scRNAseq respiratory system datasets, facilitating disease comparisons at the single-cell level with the potential to identify novel targets for intervention [ 74 ].…”
Section: Hot Topic: What Did You Always Want To Know About Omics Anal...mentioning
confidence: 99%